Transforming Learning in Primary Schools: The Role of AI and Flipped Classroom-based Apps - Rindaningsih, Ida; Mustaqim, Ilmawan; Indra, Ika Ratna; Astuti, Ruli (Universitas Dharma Wacana, 2024)
In today's digital era, the flipped classroom is gaining popularity for its ability to increase student engagement and meaningful learning. In the flipped classroom, there are learning videos and assignments given to students to study at home. For this reason, a simple and adaptive application is needed for students to use. Referring to this, it is known that in several regions in Indonesia there are still schools and communities that are not adaptive to technological developments and are still considered complicated and confusing. For this reason, this article aims to test the effectiveness of flipped classroom-based learning applications by applying joyfull learning for elementary school students. This research uses a quasiexperimental version of the control group design, the factorial analysis technique of 2x2 nonequivalent design used Analysis of Variance (ANOVA). The results showed that there was a very significant difference in learning outcomes for Aqidah akhlak subjects in the experimental class and control class. And there is an interaction between Joyfull learning and Flipped classroom application based on Flipped classroom on student learning outcomes. The findings of this study are that the kelasbalik.id application is very adaptive for teachers, parents, and students who are gaptek so that it can improve students' learning experience